MERANCANG LEMBAGA KEUANGAN MIKRO SYARIAH YANG TEPAT PADA DESA CIBITUNG WETAN, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Thantawi, Tubagus Rifqy; Anwar, Miftakhul; Imanudin , Teguh (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2023)
The Cibitung Wetan Village development program to improve the economy is carried out with various kinds of community empowerment programs, one of which is with Islamic microfinance literacy activities. problems from partners include aspects of financial management. The method used is theoretical and practical training. The result of this community service activity is that partners have the ability to manage financial management, then some of the public and marketing personnel these microfinance institutions establish good cooperation to improve the economy family.